Laparoscopic Nephrectomy versus Open Nephrectomy for Patients with Autosomal Dominant Polycystic Kidney Disease: A Systematic Review and Meta-Analysis - Guo, Pengyu; Xu, Wanhai; Li, Huibo; Ren, Tong; Ni, Shaobin; Ren, Minghua (PLOS ONE, 2015)
Objective To compare efficacy and safety of laparoscopicnephrectomy (LN) versusopen nephrectomy (ON) in the management of autosomal dominant polycystic kidney disease (ADPKD), we conducted a systematic review and meta-analysis. Methods A systematic search of the electronic databases PubMed, Scopus, and the Cochrane Library was performed up to October 2014.This systematic review was performed based on observational comparative studies that assessed the two techniques. The weighted mean difference (WMD) and risk ratio (RR), with their corresponding 95% confidence interval (CI), were calculated to compare continuous and dichotomous variables, respectively. Results Seven studies were identified, including 195 cases (118 LN / 77 ON). Although LN was associated with longer operative time (WMD 30.236, 95%CI 14.541 −45.932, P<0.001) and the specimen might not have been resected as heavy as the ON group (WMD -986.516, 95%CI -1883.24–-89.795, P = 0.031), patients in this group might benefit from a shorter length of hospital stay (WMD -3.576, 95%CI 4.976–-2.176, P <0.001), less estimated blood loss (WMD -180.245, 95%CI -317.939–-42.556, P = 0.010), and lower need of transfusion (RR 0.345, 95%CI 0.183–0.650, P = 0.001). The LN group also had less overall complications (RR 0.545, 95%CI 0.329–0.903, P = 0.018). The need of narcotic analgesics between the two groups might have no significant difference (WMD -54.66, 95%CI -129.76–20.44, P = 0.154). Conclusion LN for giant symptomatic ADPKD was feasible, safe and efficacious. Morbidity was significantly reduced compared with the open approach. For an experienced laparoscopist, LN might be a better alternative.